2019
DOI: 10.1111/1365-2656.13138
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic costs of altered growth trajectories across life transitions in amphibians

Abstract: Climate change is causing increases in temperature and in the frequency of extreme weather events. Under this scenario, organisms should maintain or develop strategies to cope with environmental fluctuations, such as the capacity to modify growth trajectories. However, altering growth can have negative consequences for organisms’ fitness. Here, we investigated the metabolic alterations induced by compensatory growth during the larval development of the common frog (Rana temporaria), quantifying changes in oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 74 publications
(120 reference statements)
2
53
0
Order By: Relevance
“…Guerra, Zenteno‐Savín, Maeda‐Martínez, Philipp, & Abele, 2012), amphibians (e.g. Burraco, Valdés, & Orizaola, 2020), and reptiles (e.g. Furtado‐Filho, Polcheira, Machado, Mourão, & Hermes‐Lima, 2007).…”
Section: Global Warming Fast Growth and Ageing In Ectothermsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guerra, Zenteno‐Savín, Maeda‐Martínez, Philipp, & Abele, 2012), amphibians (e.g. Burraco, Valdés, & Orizaola, 2020), and reptiles (e.g. Furtado‐Filho, Polcheira, Machado, Mourão, & Hermes‐Lima, 2007).…”
Section: Global Warming Fast Growth and Ageing In Ectothermsmentioning
confidence: 99%
“…Heritability estimates for telomere length in animals range from 0.18 to >1 (reviewed in Dugdale & Richardson, 2018; Haussmann & Heidinger, 2015; Reichert et al., 2015), tending to be higher when measured earlier in life (Dugdale & Richardson, 2018). However, in ectotherms (in contrast to most endotherms), telomeres show signs of elongation after birth in several species (reptiles: Ujvari et al., 2017; fish: McLennan et al., 2018; amphibians: Burraco et al., 2020). This makes it far from straightforward to decide the point in ontogeny at which telomere length should be compared between parents and offspring.…”
Section: Intergenerational Effects Of Climate Change On Ageing Rates mentioning
confidence: 99%
“…An extensive (but not exhaustive) meta-analysis identified these phenomena in 38 mammalian, 91 piscine, 39 avian and 30 arthropod species (Hector and Nakagawa, 2012). While not analyzed in this study, compensatory growth also occurs in amphibians and reptiles -e.g., Roark et al (2009) and Burraco et al (2019). Interestingly, the evolutionarily highly conserved nature of compensatory or catch-up growth suggests a high degree of biological significance.…”
Section: Humansmentioning
confidence: 99%
“…Yet, as for fast life history in general, there is ongoing debate about the role of oxidative stress in shaping rapid growth and its costs (Christensen et al., 2016; Monaghan & Ozanne, 2018; Smith et al., 2016). While several studies showed compensatory growth to be associated with increased oxidative stress (but see Noguera, Lores, Alonso‐Alvarez, & Velando, 2011), this was mainly based on the levels of antioxidant enzymes (birds: Alonso‐Alvarez, Bertrand, Faivre, & Sorci, 2007; fish: Costantini et al., 2018; damselflies: De Block & Stoks, 2008; ladybirds: Xie et al., 2015; frogs: Burraco, Valdés, & Orizaola, 2020) and very rarely on the direct measurement of oxidative damage (fish: Kim, Noguera, & Velando, 2019; birds: Costantini et al., 2018). Therefore, current evidence is largely inconclusive because levels of antioxidant defence may covary both negatively as positively with oxidative damage (Costantini & Verhulst, 2009).…”
Section: Introductionmentioning
confidence: 99%